Micro-Foundations of Fragility: Concepts, Measurement and Application - Ghassan Baliki; Tilman Brück; Neil T.N. Ferguson; Sindu W. Kebede (Institute of Labor Economics (IZA), 2017)
We explore the micro-foundations of fragility by discussing how to measure the exposure to fragility at the individual level. We focus on two notions that are not covered by existing aggregate, state-centric indicators of fragility. First, different individuals may experience fragility very differently. Second, even though a country as a whole may not be "fragile", individuals may be exposed to fragility. This differentiation suggests that the experience of fragility varies not just at national levels but also between districts and between individuals. To test this idea, we propose a "Fragility Exposure Index", which accounts for human security, economic inclusion and social cohesion at the micro-level. We then derive a series of metrics that can be collected in typical household surveys. We test the performance of the Fragility Exposure Index by including a "Fragility Exposure Module" in a household survey in Kenya. Analysis of this data shows that individuals living in rural areas, as well as young and single individuals, exhibit greater exposure to fragility. These findings demonstrate the importance of understanding fragility at the individual level, particularly as it provides the basis to understanding which who would benefit most from pro-stability interventions and to how these interventions perform.
Keywords: O12; O17; 330; institutions; transition; fragility; households; surveys